2010
DOI: 10.1194/jlr.m008060
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and reduced prostaglandin synthesis in skeletal muscle of Group VIB Ca2+-independent phospholipase A2γ-deficient mice

Abstract: Supplementary key words cardiolipin • mitochondria • muscle • phospholipidsPhospholipase A 2 (PLA 2 ) enzymes catalyze the cleavage of the sn -2 ester bond of glycerophospholipids to yield free fatty acids and lysophospholipids, thereby playing critical roles in cellular lipid metabolisms linked to energy storage, membrane remodeling, and lipid mediator signaling. In the membrane remodeling reaction, fatty acyl groups are fi rst removed (deacylated) by PLA 2 and then replaced (reacylated) with different fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 71 publications
3
45
0
Order By: Relevance
“…Excretion-General phenotypic features of mice null for iPLA 2 ␥ were described previously (7,11). In keeping with the earlier report, modest growth retardation was visible in KO mice after 2 months of age.…”
Section: Ipla 2 ␥ Deletion Does Not Affect Baseline Urinary Albuminsupporting
confidence: 61%
See 3 more Smart Citations
“…Excretion-General phenotypic features of mice null for iPLA 2 ␥ were described previously (7,11). In keeping with the earlier report, modest growth retardation was visible in KO mice after 2 months of age.…”
Section: Ipla 2 ␥ Deletion Does Not Affect Baseline Urinary Albuminsupporting
confidence: 61%
“…Our results in podocytes are in keeping with previous studies, where deletion of iPLA 2 ␥ in mice resulted in mitochondrial disruption. For example, deletion of iPLA 2 ␥ induced mitochondrial dysfunction in the heart, skeletal muscle, liver, and brain (7,8,10,11). iPLA 2 ␥ KO mice displayed cold intolerance, a defect in mitochondrial cytochrome oxidase, and multiple bioenergetic dysfunctional phenotypes at 4 -6 months of age (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass Spectrometric Analysis of Myocardial Eicosanoids, Docosanoids, and Oxidized Linoleic Acids-Previous studies have demonstrated the important roles of iPLA 2 ␥ in releasing polyunsaturated fatty acids from mitochondria that are subsequently oxidized by a wide variety of downstream oxygenases (32)(33)(34)(35). To gain access to the extremely low abundance regime necessary for accurate identification and quantification of oxidized fatty acids in myocardium, we used charge-switch derivatization with multiple reaction monitoring (MRM) in conjunction with high mass accuracy analysis of signature product ions from diagnostic transitions (36).…”
Section: Resultsmentioning
confidence: 99%